Enhancing Arabic Vocabulary Acquisition in Second Grade: The Efficacy of the Singing Method - Rahmad, Harnowo Pinilih; Anwar , Najih (Indonesian Journal of Islamic Studies, 2024)
This study investigates the implementation of the singing method in learning Arabic vocabulary among second-grade students at Muhammadiyah 1 Elementary School, Malang. Employing a descriptive qualitative approach, data was gathered through observation, documentation, and interviews. The study reveals a structured three-stage process of planning, implementing, and evaluating the singing method. Enthusiastic student engagement, teacher familiarity with singing activities, and the use of the al-ashri book as media emerged as supportive factors. Conversely, inhibiting factors included student disruptions, reluctance to participate, and silent lip movement during singing. Proposed solutions encompass teacher creativity in presenting vocabulary songs, effective classroom management, incorporation of music, videos, and movements, and group singing activities. This research underscores the effectiveness of the singing method in fostering Arabic vocabulary acquisition, offering valuable insights for language educators. Highlight: This study assesses the efficacy of the singing method in Arabic vocabulary acquisition among second-grade students, providing valuable insights for language educators. Employing a descriptive qualitative approach, the research reveals a structured three-stage process—planning, implementing, and evaluating—for the effective implementation of the singing method. Supportive factors, including enthusiastic student engagement, teacher familiarity with singing activities, and the utilization of the al-ashri book as instructional media, contribute to the success of the method. Inhibiting factors, such as student disruptions and reluctance to participate, call for creative teacher interventions and effective classroom management strategies, emphasizing the importance of dynamic and engaging language education practices. Keyword: Singing Method, Arabic Vocabulary Learning, Second-Grade Students, Language Education, Pedagogical Strategies